Estimating baseline rates of adverse perinatal and neonatal outcomes using a facility-based surveillance approach: A prospective observational study from the WHO Global Vaccine Safety Multi-Country Collaboration on safety in pregnancy. (August 2022) - Sharan, Apoorva; Stuurman, Anke L.; Jahagirdar, Shubhashri; Elango, Varalakshmi; Riera-Montes, Margarita; Kashyap, Neeraj Kumar; Biccler, Jorne; Poluru, Ramesh; Arora, Narendra Kumar; Mathai, Mathews; Mangtani, Punam; Devlieger, Hugo; et al.
Summary: Background: Most perinatal and neonatal deaths occur in low- and middle-income countries (LMICs), yet, quality data on burden of adverse outcomes of pregnancy is limited in such countries. Methods: A network of 21 maternity units, across seven countries, undertook surveillance for low birthweight, preterm birth, small for gestational age (SGA), stillbirths, congenital microcephaly, in-hospital neonatal deaths, and neonatal infections in a cohort of over 85, 000 births from May 2019 - August 2020. For each outcome, site-specific rates per 1, 000 livebirths (or per 1, 000 total births for stillbirth) and 95% confidence intervals (CI) were calculated. Descriptive sensitivity analysis was conducted to gain insight regarding underreporting of four outcomes at 16 sites. Findings: Estimated rates varied across countries and sites, ranging between 43·3-329·5 and 21·4-276·6/1000 livebirths for low birthweight and preterm birth respectively and 11·8-81/1, 000 livebirths for SGA. No cases of congenital microcephaly were reported by three sites while the highest estimated rate was 13/1, 000 livebirths. Neonatal infection and neonatal death rates varied between 1·8-73 and 0-59·9/1000 livebirths respectively while stillbirth rates ranged between 0-57·1/1000 total births across study sites. Results from the sensitivity analysis confirmed the underreporting of congenital microcephaly and SGA in our study. Interpretation: Our study establishes site-specific baseline rates for important adverse perinatal and neonatal outcomes and addresses a critical evidence gap towards improved monitoring of benefits and risks of emerging pregnancy and neonatal interventions. Funding: The study was sponsored by the World Health Organization with funding from the Bill and Melinda Gates Foundation.